On the possibility of neutrino flavor identification at the highest energies - Supanitsky, Alberto Daniel (2012)
High energy astrophysical neutrinos carry relevant information about the origin and propagation of cosmic rays. They can be created as a by-product of the interactions of cosmic rays in the sources and during propagation of these high energy particles through the intergalactic medium. The determination of flavor composition in this high energy flux is important because it presents a unique chance to probe our understanding of neutrino flavor oscillations at gamma factors >10^21. In this work we develop a new statistical technique to study the flavor composition of the incident neutrino flux, which is based on the multipeak structure of the longitudinal profiles of very deep electron and tau neutrino horizontal air showers. Although these longitudinal profiles can be observed by means of fluorescence telescopes placed over the Earth´s surface, orbital detectors are more suitable for neutrino observations owing to their much larger aperture. Therefore, we focus on the high energy region of the neutrino spectrum relevant for observations with orbital detectors like the planned JEM-EUSO telescope.